Effect of olfactory ensheathing cells (OECs) transplantation on functional recovery in acute phase of spinal contused rats - Somayeh Heidarizadi; Naser Abbasi; Khairollah Asadollahi; Sara Rezaei; Ardeshir Moayeri; Monireh Azizi (Journal of Basic Research in Medical Sciences, 2017)
Introduction: Spinal cord injuries (SCI) lead to permanent irreversible functional deficits.  Poor prognosis of patients is the motivation of searching a treatment for the chronic injury.  Planting stem cells provides us with a promising strategy. In the meanwhile, the use of olfactory ensheathing cells (OECs) has shown very good results.  This study aims at evaluating the effect of transplanted OECs on functional recovery of acute SCI in rats.